Ocena sytuacji finansowej firmy POLDANOR S.A. w latach 2010–2011: Evaluation of the financial situation of POLDANOR S.A. in the period 2010-2011 - Przesmycka, Agnieszka; Podstawka, Marian (Management and Administration Journal, 2021)
Poldanor S.A. is a company in good financial situation. From the perspective of its effectiveness, the company uses mercantile credits, but at low level. The company itself offers long term period of payment. Stocks are renewed on average more than 3 times a year. Poldanor S.A. is a profitable company that earns on each level of its activity what testifies to good potential of firm. Poldanor S.A. also uses the positive effects of financial leverage. The solvency rates show that the level of liabilities of the company is kept on the safe level and Poldanor S.A. has no problems with repayment of the interest and capital from the credit. Pursuant to the available data from the financial statements and the scope of the presented analysis the company has to be assessed positively.